2016
DOI: 10.1515/rela-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the pronunciation of sentence final and word boundary stops to French learners of English: distracted imitation versus audio-visual explanations

Abstract: AbstractStudies on stop unrelease in second language acquisition have hitherto focused on the productions of Slavic learners of English (Šimáčková & Podlipský, 2015) and experiments on Polish learners of English; the latter show the tendency to release stops on a more regular basis depending on the type of stop combinations (Rojczyk et al. 2013). In the present study, we aim to test the efficiency of audio-visual explanations as opposed to distracted imitation in pronunciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This study examined whether observing hand gestures mimicking the aspiration feature of aspirated consonants can facilitate the initial-stage learning of nonnative consonants from two complementary dimensions, namely, the perception of aspirated and unaspirated consonants (which was examined through an identification task) and the production of the aspiration contrasts (which was tested through an imitation task). While previous studies have shown beneficial effects of pitch gestures on the learning of suprasegmental features, such as lexical tones (e.g., Baills et al, 2019) and intonation patterns (Yuan et al, 2019), and also beneficial effects of beat gestures on rhythmic patterns (Gluhareva & Prieto, 2017), more inconsistent results have been found for the role of phonetically based gestures on the learning of L2 segmental phonology (Amand & Touhami, 2016;Hoetjes et al, 2019). Crucially, this study examined whether the appropriateness of the gesture relative to the phonetic features of the aspirated consonants would impact, in any way, the training effect.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This study examined whether observing hand gestures mimicking the aspiration feature of aspirated consonants can facilitate the initial-stage learning of nonnative consonants from two complementary dimensions, namely, the perception of aspirated and unaspirated consonants (which was examined through an identification task) and the production of the aspiration contrasts (which was tested through an imitation task). While previous studies have shown beneficial effects of pitch gestures on the learning of suprasegmental features, such as lexical tones (e.g., Baills et al, 2019) and intonation patterns (Yuan et al, 2019), and also beneficial effects of beat gestures on rhythmic patterns (Gluhareva & Prieto, 2017), more inconsistent results have been found for the role of phonetically based gestures on the learning of L2 segmental phonology (Amand & Touhami, 2016;Hoetjes et al, 2019). Crucially, this study examined whether the appropriateness of the gesture relative to the phonetic features of the aspirated consonants would impact, in any way, the training effect.…”
Section: Discussionmentioning
confidence: 95%
“…Considering that the hand burst gesture matched the aspiration feature of the plosive only, these results strongly suggest that gestures may enhance the learning of nonnative segments only when they appropriately depict the phonetic information of the target segments. production of released and unreleased stops in English (Amand & Touhami, 2016), as well as the Spanish phoneme /u/ (Hoetjes et al, 2019), this was not the case when the technique was applied to Spanish /θ/ (Hoetjes et al, 2019). In our view, while the gestures used for English stops and the Spanish phoneme /u/ provide clearly visible articulatory information about the target sound, this is not the case for the gesture used for the phoneme /θ/, which depicts the tongue shape during the production of this consonant but lacks crucial information about the location of the tongue relative to the teeth or jaw aperture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations